HIGH-PERFORMANCE LIQUID CHROMATOGRAPHIC ESTIMATION METHOD FOR TRANSDERMAL DIFFUSION STUDY OF GRANISETRON - BUKKA, RAMA; HN, CHAYA (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: The study is aimed to develop a simple, isocratic and sensitive reversed-phase high-performance liquid chromatography method for the analysis of granisetron during transdermal permeation studies through porcine ear epithelium. Methods: A reversed-phase (C18) column was used with ultraviolet detection at 210 nm. Selected mobile phase contained 25% (v/v) of acetonitrile and 75% (v/v) of 0.25 mM potassium dihydrogen orthophosphate solution pH adjusted to 3.0 using 1% orthophosphoric acid solution. Results: Calibration curve showed good linearity over 0.1–30 μg/mL concentration range of porcine ear permeates in 80% ethanol and 20% water (blank permeates). The applicability of the method was demonstrated by the analysis of diffusion study samples of granisetron through porcine ear epithelium and the steady-state permeability flux (J) from ethanolic solution was found to be 4.707 µg/square cm/h. Conclusion: The developed method can be used in the analysis of diffusion study samples of granisetron transdermal formulations through the porcine ear epithelium.